Quantification of the Effect of Citrulline and Homocitrulline Residues on the Collision-Induced Fragmentation of Peptides - Steckel, Arnold (J Am Soc Mass Spectrom, 2020)
[Image: see text] Posttranslational modifications of proteins like citrullination and carbamylation are associated with several diseases. Detailed analytical characterization of citrullinated and carbamylated proteins or peptides could be difficult due to the low concentration of the analytes in complex biological samples. High structural similarity and chemical behavior of citrullinated and carbamylated residues also pose a challenge. We previously reported the “citrulline effect” phenomenon that is manifested in the generation of intense y type ions originating from Cit-Zzz amide bond scissions in collision-induced dissociation tandem mass spectra of citrullinated tryptic peptides. In this study, we created a rigorous tryptic-like model system of both citrulline and homocitrulline-containing peptides that included appropriate and well-defined controls and fragment analogues to quantify the citrulline effect and investigate whether there is an effect for homocitrulline residues as well. Our results show that citrulline residues significantly increased fragmentation at their C-terminus relatively independent of the identity of the following amino acid. In comparison, homocitrulline residues displayed inconclusive results at the same energies. However, the strength of effects was dependent on collision energy and the position of citrulline and homocitrulline in the sequences. As newer software algorithms tend to observe structure–intensity relationships during annotation, this finding increases reliable identification of modified proteins/peptides.